Developing Flashcard to Teach Students' Integrated Listening and Speaking Skills for Seventh Grader - Tiara Prameswari, Dyah ayu; Hermayawati, Hermayawati ((JELE) Journal Of English Language and Education, 2019)
This study is aimed to help students in learning integrated listening-speaking skills by developing flash card as teaching media. It is found that they are not supported by appropriate media and causes their motivation and competence seem to be stagnant. It is also found that there are some weaknesses on the old media. Start from the design that is not up to date and seems not so interesting fro the students. Then the materials of the media that are assumed as fragile because it is made of paper. The size of the media that is seen as too small and the procedure of the use that sometimes made teachers find difficulties to use it. Regarding to those findings, this research goes further to design the new media in order to solve those problems. This research adopted Research and Development (R&D) with ADDIE model. After implementation, it is found that the product has development and some strength that can be beneficial for the users.